Validating a Parental Trauma Informed Approaches Scale in Low-Income Countries Using the Rasch Model - Efstratopoulou, M; Opoku, MP; Tsingilis, N; Nur, S; Gyimah, EM; Moustafa, A (Elsevier, 2025)
Low-income countries, such as Bangladesh, Egypt and Nepal, are experiencing enormous social problems, such as poverty, violence and extremism, which can expose children to trauma. However, the literature on parental awareness of trauma-informed approaches is very limited, possibly due to the lack of a reliable instrument for continuous data collection on parental knowledge regarding the onset of trauma and the best management strategies. The overarching aim of this study was to thoroughly validate the parental trauma identification and management scale (PTIMS), a newly developed tool for trauma-informed approaches, using data collected from parents in three low-income countries. A total of 750 parents from three low-income countries (Bangladesh, n = 300; Egypt, n = 205; Nepal, n = 245) shared experiences of poverty and social problems that could increase their children's vulnerability to trauma. The parents completed the PTIMS, which was translated into the first language of each of the studied countries and subjected to validation using item response theory. Multivariate analysis of variance was computed to understand the differences between participants. Rasch analysis yielded appropriate psychometric properties for the PTIMS. For example, the outfit mean square and infit mean square values of all 33 items ranged from 0.878 to 1.124 and from 0.910 to 1.096, respectively. The multivariate analysis of variance revealed differences between participants in some demographic variables, such as country, age, employment status and school type. The PTIMS is a valid instrument for gathering surveillance data on trauma awareness among parents, who are important stakeholders in efforts to create trauma-informed schools in low-income contexts.
Keywords: 4404 Development Studies; 44 Human Society; Physical Injury - Accidents and Adverse Effects; Behavioral and Social Science; Basic Behavioral and Social Science; Social Determinants of Health; Pediatric Research Initiative; 1 No Poverty; 1402 Applied Economics; 1607 Social Work; Social Work; 4409 Social work; 4410 Sociology; Parents; Trauma; School; Bangladesh; Egypt; Nepal